Stress Tolerance in Doughs of Saccharomyces cerevisiae Trehalase Mutants Derived from Commercial Baker’s Yeast - Shima, Jun (American Society for Microbiology, 1999)
Accumulation of trehalose is widely believed to be a critical determinant in improving the stress tolerance of the yeast Saccharomyces cerevisiae, which is commonly used in commercial bread dough. To retain the accumulation of trehalose in yeast cells, we constructed, for the first time, diploid homozygous neutral trehalase mutants (Δnth1), acid trehalase mutants (Δath1), and double mutants (Δnth1 ath1) by using commercial baker’s yeast strains as the parent strains and the gene disruption method. During fermentation in a liquid fermentation medium, degradation of intracellular trehalose was inhibited with all of the trehalase mutants. The gassing power of frozen doughs made with these mutants was greater than the gassing power of doughs made with the parent strains. The Δnth1 and Δath1 strains also exhibited higher levels of tolerance of dry conditions than the parent strains exhibited; however, the Δnth1 ath1 strain exhibited lower tolerance of dry conditions than the parent strain exhibited. The improved freeze tolerance exhibited by all of the trehalase mutants may make these strains useful in frozen dough.